Acoustoelectric properties of graphene under the influence of saw and external electric field - Insepov, Z.; Tynyshtykbayev, Kurbangali B.; Kononenko, Oleg V.; Roshchupkin, Dmitry V. (Nazarbayev University, NURIS, Institute of Microelectronics Technology and High Purity Materials, 2015)
The effect of SAW on the electrical properties of the few-layer (2-3 layers) graphene is studied. Under the influence of SAW the appearence of acoustoelectric current IAEC in graphene is observed. The sign and magnitude of the induced IAEC in graphene conditioned by magnitude and direction of the electromagnetic fields induced by SAW and an external electric field. When the direction of SAW and Vbias is the same IAEC amplified, when at the opposite direction - IAEC are reduced in result of the interaction of these fields with each other. As a result of the measurement of the induced acoustoelectric (IAEC) current in graphene under the influence of a surface acoustic wave (SAW) the fluctuation nature of acoustoelectric current in the area of electrical neutrality is established at low voltages of an external bias (Vbias) applied on a graphene. The fluctuation character of the IAEC is manifested in all cases of measurements depending on the action of SAW and Vbias near the point of electrical neutrality. Chaotic fluctuation potential of graphene in the area of electrical neutrality is enhanced by the action of SAW that allows observing it in real conditions of the experiment at room temperature in air. The magnitude of IAEC depends on the power of SAW, while there is a parabolic dependence of the induced IAEC on the amplification current of SAW power (ISAW). The parabolic dependence of IAEC on ISAW explained by specific relaxation of acoustic phonons of the piezocrystallical substrate, which is dominant in the process of electronphonon scattering in graphene and acoustoelectric current induction in it. For large magnitudes of Vbias strict linear dependence of the IAEC on Vbias is observed. Large Vbias effectively suppress the appearance of the fluctuation potential of electrons and holes. The ability to control the magnitude and direction of IAEC induced in graphene by SAW is of practical importance.
Keywords: SAW; acoustoelectric current; surface acoustic wave; voltage bias; graphene